1984
DOI: 10.1111/j.1524-4725.1984.tb01339.x
|View full text |Cite
|
Sign up to set email alerts
|

Microcystic Adnexal Carcinoma Treated by Microscopically Controlled Excision

Abstract: Microcystic adnexal carcinoma is a distinct clinicopathologic entity with combined pilar and eccrine differentiation. Clinically it resembles other adnexal neoplasms, but it tends to be deeply invasive and locally aggressive. A 47-year-old man with microcystic adnexal carcinoma of the left cheek with deep dermal and subcutaneous invasion was successfully treated by microscopically controlled excision. The possible etiologic association with teenage radiation therapy is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

1986
1986
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 3 publications
0
25
0
Order By: Relevance
“…History of radiotherapy for acne prior to the development of MAC has been reported in only two cases by Cooper and Mills 7 and Fleischmann et al 8 Therefore, radiotherapy does not appear to be a significant predisposing factor in the development of MAC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…History of radiotherapy for acne prior to the development of MAC has been reported in only two cases by Cooper and Mills 7 and Fleischmann et al 8 Therefore, radiotherapy does not appear to be a significant predisposing factor in the development of MAC.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment has included local wide excision, radiation alone, 10 excision followed by radiation, 1 and Mohs surgery 6–8 . Of 15 patients reported by Cooper et al, 2 9 (60%) had one or more recurrences after initial surgical excision.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The female predominance that was evident in our study has been observed, albeit inconsistently, in other series. 14,[18][19][20]23,24 Again, women also appeared to be affected at an older age than men. This age-sex interaction seems to be common among other adnexal neoplasms, especially syringomas and trichoblastomas.…”
Section: Commentmentioning
confidence: 99%
“…These recurrences might be secondary to an initial lack of recognition of the tendency for aggressive peripheral and deep invasion by these tumors, resulting in inadequate surgical excision or radiation treatment. Mohs micrographically controlled surgery offers several advantages for treatment of these tumors, as has been reported previously 3 …”
Section: Discussionmentioning
confidence: 75%